Analisis EIGRP Metric Dalam Penentuan Jalur Terbaik Pada Jaringan - Oris Krianto Sulaiman (STMIK Budi Darma, 2021)
In managing a large network, it takes the ability to manage the network so that traffic is good. To connect to such a large network requires many routers, each router will connect to one another. But the best choice of any router is required for network traffic efficiency. There are two routing protocols that can be used, namely static routing and dynamic routing. EIGRP is dynamic routing which, principally between routers, can communicate directly and dynamically, so that when there is a new router in a network, routers can communicate directly because they can exchange information. EIGRP uses the Diffussing Update Algorithm (DUAL) in determining the best path. In this study, EIGRP metrics will be analyzed to try the best path on the network by sending Internet Control Message Protocol (ICMP) packets. There are two networks that will be tested with differences in the Fast Ethernet bandwidth interface of each router. This experiment resulted in different values between Fast Ethernet default bandwidth and non-default bandwidth, so that the value of the variable affects the selection of the best path of network traffic